Gipsy (Rome) population in Czechoslovakia - Kauerova, V (Demosta, 1983)
Over 200,00 gypsies live in Czechoslovakia, or about 4% of the population of the Slovak Socialist Republic. The gypsy population grew by 25.5% from 1971-1981, while the total popualtion grew by 10%. The sex ratio of 1033 men to 1000 women is a distinct characteristic of the gypsy population. The proportion of gypsy children ages 0-14 is also very high, about 43.4% of the total gypsy population. The male average age is 10.1; the female average age is 11.3. In 1980, the proportion of gypsies with basic educational attainment reached 81.9%, while in 1970 it was less than a third of those over 15. Their employment grew by 9.8% from 1970-1980; women's employment, and especially married women's employment, also inceased. In occupations, 83.4% of gypsies are manual workers, 6.8% are employers, 8.8 belong to production cooperatives, and 1% are in other occupations. Of the 47,117 gypsy households in the Slovak Socialist Republic, 44% have more than 5 members, and 11.6% have more than 8 members. Gypsy housing remains on a low level, with 59% living in apartments with inconvenient access to equipment and facilities and 36.3% living in 1 room flats. In spite of systematic care from a socialist society, gyspies' housing has only improved partially, and considerable differences remain between their housing and that of the rest of the population.
Keywords: kultura; Ethnicity; Demographic Factors; vyspělé země; Europe; poměr pohlaví; Population Density; Europe, Eastern; Czechoslovakia; Evropa; Československo; stupeň vzdělání; hustota populace; Population Characteristics; Developed Countries; východní Evropa; bydlení; Ethnic Groups; zaměstnanost; populace; Culture; Demography; Housing; etnicita; demografie; Population Size; Population; populační charakteristiky; Employment Status; Occupational Status; Sex Ratio; Cultural Background; Educational Status; Eastern Europe; Employment; Tribes